New pole-changing windings with improved electromagnetic properties - Dauletbek A. Rismuxamedov; Husniddin F. Shamsutdinov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: at present, special attention is paid to the creation of new energy- and resource-saving electric drives that make it possible to increase the service life of active parts of mechanisms by facilitating the start-up process and simplifying the technological process by ensuring precise stopping of high-inertia grinding and lifting and transport mechanisms. Scientific research is being conducted to improve the performance characteristics of existing electric drives by upgrading these mechanisms using adjustable electric drives. In this area, one of the priority tasks is to develop adjustable electric drives based on multi-speed motors that meet the requirements of electric drives for grinding and lifting and transport mechanisms. Aim: development of pole-changing winding circuits with improved electromagnetic properties and simplified manufacturing technology. Methods: to develop new circuits with pole-changing windings, the method of Discretely Given Spatial Functions was used, in which the currents are uniformly distributed across the stator slots. Results: based on the results of scientific research, a three-phase pole-changing winding with a stator slot number of 48 and a pole ratio of 8/4 has been developed. Analysis of the electromagnetic composition of the newly developed winding shows that the higher harmonic components are minimal, the shape of the Goerges diagram is close to a circle, and the value of the differential scattering coefficient is minimal σ0=5.3%.